CD38 is the major enzyme responsible for synthesis of nicotinic acid-adenine dinucleotide phosphate in mammalian tissues. - Chini, Eduardo N (2002)
In the present study, we have determined the role of the enzyme CD38 upon the synthesis of the Ca(2+)-releasing nucleotide nicotinic acid-adenine dinucleotide phosphate (NAADP). In rat tissues, we observed that the capacity for NAADP synthesis could be co-immunoprecipitated with CD38 using an anti-CD38 antibody. Furthermore, we observed that several tissues from CD38 knockout mice had no capacity for the synthesis of this nucleotide. In addition, CD38 was also identified as the major enzyme responsible for the synthesis of the second messenger cyclic ADP-ribose. These observations lead to the conclusion that CD38 is the major enzyme responsible for the synthesis of NAADP and cyclic ADP-ribose, and raises the possibility of a new signalling pathway where two different Ca(2+)-releasing nucleotides are synthesized by the same enzyme.